The Influence of Push-Pull-Mooring Effects on E-Wallet Customer Switching in Generation Z in DKI Jakarta - Yunita, Eka; Munandar, Jono Mintarto (The South East Asian Journal of Management, 2023)
Research Aims: This research aims to identify the characteristics of Generation Z e-wallet customers in DKI Jakarta; analyse the effect of push-pull-mooring effects on switching intention, the moderating effect of the mooring effects on the relationship between push effects and pull effects with switching intention, and the effect of switching intention on the switching behaviour of Generation Z e-wallet customers. Design/Methodology/Approach: There were 262 respondents, using non-probability sampling with the purposive sampling method. The data analysis technique used is descriptive analysis and SEM-PLS. Research Findings: The results of this study indicate that the push effects do not affect switching intention. Pull and mooring effects positively and significantly affect switching intention. Mooring effects positively and significantly affect switching intention and behaviour. Mooring effects cannot moderate the relationship between push and pull effects to switching intention. Switching intention has a positive and significant effect on switching behaviour. Theoretical Contribution/Originality: This study discusses the influence of the push-pull-mooring effect on customers switching from one e-wallet brand to another, especially in the Z generation, who are very close to technology. Managerial Implication in the South East Asian Context: To increase the pull effect to get the customer's attention back in Southeast Asia with Indonesia as a reference (provide the discount, cashback, and promotional events), increasing mooring effects by creating strong relationships with customers through the convenience and benefits provided by using an e-wallet (loyalty program, e-mail marketing, respond quickly to consumer consultations). Research Limitation & Implications: This research is limited to Generation Z and e-wallet products. Sampling in this study is also only from Jakarta.